Dehydroepiandrosterone attenuates LPS-induced inflammatory responses via activation of Nrf2 in RAW264.7 macrophages. (March 2021) - Cao, Ji; Li, Qian; Shen, Xuehuai; Yao, Yao; Li, Longlong; Ma, Haitian
Graphical abstract: Highlights: DHEA blocked the LPS-mediated PI3K-AKT, MAPK and NF-κB activation. DHEA alleviated the redox imbalance and decreased the reactive oxygen species production. DHEA enhanced autophagy through the regulation of AKT-mTOR signaling. DHEA activated the Nrf2 signaling to inhibit the inflammatory responses. Abstract: Dehydroepiandrosterone (DHEA) is the major steroid hormone in humans and animals, which can regulate the body's inflammatory responses. However, the detail mechanism of this beneficial function is still poorly understood. The present study aimed to explore the anti-inflammation effect of DHEA and its underlying molecular mechanism in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages. The findings showed that DHEA significantly inhibited the inflammation-related mediators production and pro-inflammatory cytokines expression level. Further research found that DHEA obviously blocked the LPS-stimulated PI3K/AKT, MAPK and NF-κB activation in RAW 264.7 cells. Meanwhile, DHEA enhanced the autophagy-dependent Keap1 protein degradation, subsequently activated the Nrf2 pathway to alleviate the redox imbalance and inflammatory responses. In conclusion, our data demonstrated that DHEA suppresses inflammatory responses through the activation of Nrf2 and inhibition of NF-κB in LPS-stimulated macrophages.